Generalized trust, helpfulness, fairness and growth in european countries a revised analysis - Jacek J. Sztaudynger; Ewa Ambroziak; Paweł Starosta (Comparative Economic Research. Central and Eastern Europe, 2022)
This research is an attempt to assess the impact of trust, helpfulness, and fairness on economic growth in Europe. The first part of the paper highlights the concept of social capital and the related concept of trust, while the second part gives an overview of selected research hitherto conducted on the subject. The third part presents an econometric growth model based on a modified Cobb-Douglas production function. The model we propose includes three interrelated variables: generalized trust, helpfulness, and fairness, which can be combined into an aggregated variable, called 'cooperation capital'. The pooled sample covers the years 2006-2018 and includes 22 European countries. European Social Survey data provides a chance to examine the previously inaccessible measurement of the impact of bridging social capital increase on economic growth. The results suggest that approximately 1/8 of economic growth (measured by the GDP growth rate) may be ascribed to the effect of an increase in cooperation capital. In addition, 86% of this effect occurs with a 1-4 year lag. The three-component cooperation capital explains economic growth better than generalized trust exclusively. The estimated model suggests that an increase in helpfulness among people has the largest impact on economic growth. As the outcomes of this research also clearly show, fairness and trust are key factors for economic growth in Europe.
Keywords: A13; C31; C33; O47; P24; Z13; 330; ing social capital; trust; helpfulness; fairness; economic growth; Europe